Pulmonary Tuberculosis and Its Prevention - Saito, Takefumi; Narita, Masahiro; Daley, Charles L.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Every year, 10 million people fall ill with tuberculosis (TB) in the world, and of those, 1.5 million people die even though it is a preventable and curable disease. As a result, TB remains the world$1 (Bs leading infectious cause of death. On the other hand, in industrialized countries, the TB incidence has fallen to a historic low, and clinicians$1 (Bexperience with TB diminished significantly in recent years. Additional challenges for clinicians include atypical presentation of TB in the immunocompromised, especially among the elderly, and an increasing number of patients with drug-resistant TB. Delayed diagnosis of TB leads to the spread of TB including nosocomial transmission because TB is an air-borne infectious disease, and suboptimal treatment can result in development of drug resistance. Furthermore, treatment of latent TB infection (LTBI) can prevent future TB cases but it has been under-utilized despite recent innovations in diagnosis and treatment regimens of LTBI. This book focuses on advances in diagnostic tools and treatment for both TB disease and latent TB infection. Each chapter/topic is written by one of the top TB experts in the field and the authors are from Japan and the US. Pulmonary Tuberculosis and its Prevention offers up-to-date information that can be incorporated into a busy practice of clinicians while they can appreciate broad international perspectives and gain in-depth knowledge on TB.s
Part I. Epidemiology and Pathogenesis -- Chapter 1. Epidemiology -- Chapter 2. Immunology -- Chapter 3. Impact of Biologic and JAK Inhibitor Therapies on TB: How do Biologic Therapies Affect the Presentation and Treatment Course of Pulmonary TB? -- Chapter 4. Advances in Mycobacterial Laboratories: What is the latest laboratory approach to diagnose and manage pulmonary tuberculosis? -- Part II Pulmonary Tuberculosis -- Chapter 5. Advances in Diagnostics of Pulmonary tuberculosis: What is the Latest Approach to Diagnose Pulmonary TB? -- Chapter 6. HRCT diagnosis of pulmonary tuberculosis: Microlesions -- Chapter 7. Advances in Treatment of Drug Resistant Pulmonary TB: What is the latest approach to treat drug-resistant pulmonary TB? -- Chapter 8. The Role of Surgical Interventions for Pulmonary TB: What is the Role of Surgical Intervention in Pulmonary TB? -- Part III Latent TB Infection: TB Prevention -- Chapter 9. Advances in Diagnosis of Latent TB Infection: What is the Latest Approach to Diagnose Latent TB Infection to Prevent TB? -- Chapter 10. Advances in Treatment of Latent TB Infection: What is the Latest Approach to Treat Latent TB Infection to Prevent Pulmonary TB? -- Part IV Research Areas -- Chapter 11. TB vaccines: What Type of TB Vaccines are Studied and will be Available in the Future? -- Chapter 12. Clinical Trials of Pulmonary TB: Challenges and Opportunities -- Chapter 13. Contributions of Japanese Scholars to Advances in Clinical Tuberculosis Management: In TB World, What Kind of Achievements are Accomplished by Japanese Researchers?.
Keywords: Internal medicine; Internal Medicine; Tuberculosis, Pulmonary -- therapy; Tuberculosis, Pulmonary -- diagnosis; Tuberculosis, Pulmonary -- prevention & control; Latent Tuberculosis -- diagnosis; Latent Tuberculosis -- therapy; Latent Tuberculosis -- prevention & control